Early Asymptomatic Decline in Left Ventricular Ejection Fraction in Adult Cancer Patients Receiving Trastuzumab - Mansoor Zeeshan; Faisal Mehmood; Zareen Gul; Maryam Khan; Ashraf, Amna; Muhammad Umair Shafique (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the frequency of Trastuzumab-induced early asymptomatic decline in left ventricular ejection fraction by serial Echocardiography and to identify various risk factors associated with cardio-toxicity.Study Design: Quasi-experimental study.Place and Duration of Study: Oncology Department, Combined Military Hospital, Lahore Pakistan, from Jan to Jun 2021.Methodology: Patients who were started on Trastuzumab-based chemotherapy and had completed at least 600 mg subcutaneously every three weeks (amounting to 17 doses) in 1 year were enrolled. Surveillance modalities include Electrocardiography, chest X-ray and Echocardiography. These were done at baseline and after four cycles of chemotherapy. All patients were evaluated for the presence of the following risk factors: diabetes mellitus, hypertension, pre-existing coronary artery disease, and chest wall. Asymptomatic cardiac dysfunction was defined as an ejection fraction (EF) fall greater than 10% on follow-up echocardiography with minimum or no symptoms.Results: The average baseline LVEF was 63.16±2.42 %, which decreased significantly to an average EF of 59.67±6.10%. In our study, 40 patients (66.7%) showed no decline in LVEF post-completion of chemotherapy. 6 patients (10.0%) showed an insignificant 10% decline in LVEF. Frequency of decline in LVEF was observed in 20 out of 60 patients (33.33%), with 14 out of 60 patients (23%) having significant (i.e., ≥10%) decline in LVEF and 6 out of 10 patients (10%) having insignificant (i.e.,≤ 10%) decline in LVEF.Conclusion: This entails regular monitoring for cardiac dysfunction by Echocardiography during Trastuzumab treatment.